Mobile-Based Digital Parenting Application to Support Children's Activities and Learning - Maskur, Shulfani; Wulandari, Sri (Universitas Putra Indonesia YPTK Padang, 2025)
Parents are often the first to respond when their children encounter learning difficulties. However, many of them struggle to determine the most appropriate strategy due to differences in each child's learning style. This study is designed to help parents identify their child's learning style (using the VARK model), create a personalized learning plan, and monitor the child's progress. The development process follows several stages of software engineering, including literature review, needs analysis, design, implementation, and system function validation. The application was developed using Flutter for the interface, Supabase for authentication and backend services, and PostgreSQL as the data storage system. Functional testing was carried out using the black-box method across key feature scenarios: login, VARK test, learning plan creation, and monitoring. The results show that the core features perform according to the development objectives, and the interface is easy to use for non-technical users. These findings highlight the potential of the application as a practical tool for parents to engage more actively in their children's learning process.